Myths on the map: the storied landscapes of Ancient Greece - Hawes, Greta ca. 20./21. Jh. (Oxford University Press, 2017)
'Myths on the Map' brings together contributions from leading scholars of Greek myth, literature, history, and archaeology to explore the intricate ways in which myth interacted with the physical and conceptual landscapes of antiquity. It highlights in particular the plurality and pervasiveness of such interactions